Upaya Pemerintah Penajam Paser Utara Dalam Pembangunan Smart City - Miswar, Miswar; Muhammad Hairul Saleh; Chik, Norlaila Abdullah (JOURNAL OF GOVERNMENT SCIENCE, 2025)
This research is about the efforts of the Penajam Paser Utara Government through the Communication and Information Service in developing a smart city. Departing from the region's potential, advantages, and capabilities, Penajam Paser Utara is one of the regions that will build its region into a smart city with innovative governance, clever branding, a smart economy, smart living, an intelligent society, and a creative environment. This type of research is qualitative descriptive research. The data in this study were obtained from field studies and literature studies. The field study used an informal and unstructured interview process with an open interview technique. Interviews were conducted with staff of the Communication and Information Office of Penajam Paser Utara Regency and several levels of society. Not only that, the researcher also conducts observations in the field by being directly involved in observing and obtaining an overview of the problems to be researched. The data analysis technique tests the resulting data to get a conclusion. The results of this study show that the Penajam Paser Utara Government is one of the regions that is building a smart city by preparing a master plan and KLHS by referring to the 2024 Work Plan. Smart city in Penajam Paser Utara builds a city that can be integrated with a touch of technology to be ready to become a smart city supported by the capabilities and potential of the region